Population Growth and Competition of Tribolium castaneum and S. oryzae in Wheat Flour - Irwan Hanafi (Eduscience Development Journal, 2023)
There are insects in their life that are pests. Most of the insect pests attack agricultural products stored in warehouses (Warehouse insects). There are more than 100 species of warehouse insects and 20 of them are cosmopolitan (Winarno, 1982). Among the barn insect species, Tribolium castaneum and S.oryzae are the most commonly found in rice, peanuts, cocoa beans, nutmeg, wheat flour, tapioca flour, copra and as a type of cake. Based on this, a study was carried out with the title "Population growth and competition of Tribolium castaneum and S.oryzae on wheat flour". the research was conducted from September to November 2022 at the Ummy Basic Laboratories. The design used was RAL with 3 (three) treatments and 3 (three) replications, the results showed that the growth of a single population of Tribolium castaneum increased with increasing time with an exponential equation Y = 9.58 e0.01202t , r = 0.37 and r2 = 0.14. For S. oryzae it decreases with the exponential equation Y=10.31 e-0.01202t